Cardiac magnetic resonance evaluation of left ventricular remodelling distribution in cardiac amyloidosis. Issue 21 (10th July 2014) - Pozo, Eduardo; Kanwar, Anubhav; Deochand, Rajiv; Castellano, Jose M; Naib, Tara; Pazos-López, Pablo; Osman, Keren; Cham, Matthew; Narula, Jagat; Fuster, Valentin; Sanz, Javier
Abstract : Background: Cardiac amyloidosis (CA) is associated with typical morphological features on echocardiography, including concentric LV hypertrophy (LVH). Cardiac magnetic resonance (CMR) can accurately depict anatomy in different cardiomyopathies. Our aim was to describe the morphological features and remodelling patterns of CA with CMR, and establish their diagnostic accuracy, as well as the value of traditional diagnostic criteria derived from echocardiography and electrocardiography. Methods: Consecutive patients referred for CMR for possible CA were retrospectively evaluated. The diagnosis of CA was established in the presence of a positive cardiac biopsy and/or a typical pattern of myocardial late gadolinium enhancement. Morphological parameters were obtained from standard cine sequences. The presence and distribution of LVH, relative wall thickness (RWT) and LV remodelling patterns were determined. Results: 130 patients (92 males (70.8%), age 64±13 years) were included. CA was diagnosed in 51 (39.2%). Patients with CA had increased LV wall thickness and LV mass index. An LV remodelling pattern different from concentric LVH was found in 42% of patients with CA, and asymmetric LVH was noted in 68.6%. A model including RWT, asymmetric LVH, and LVMI showed diagnostic accuracy of 88%, sensitivity of 67% and specificity of 86% for CA detection. Traditional diagnostic criteria for CA showed high specificity but poor sensitivity. Conclusions: Asymmetric LVH and remodelling patterns different from concentric LVH are common in CA. Increased LV mass index, increased RWT, and asymmetric LVH are independently associated with the diagnosis. Traditional diagnostic criteria show poor sensitivity.